2004
DOI: 10.1158/1078-0432.ccr-04-0349
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hepatocellular Carcinomas in vitro and Hepatic Metastases in vivo in Mice by the Histone Deacetylase Inhibitor HA-But

Abstract: Purpose:The purpose is to evaluate the CD44-mediated cellular targeting of HA-But, a hyaluronic acid esterified with butyric acid (But) residues, to hepatocellular carcinoma cell lines in vitro and to hepatic tumor metastases in vivo.Experimental Design: In vitro, the CD44-dependent cytotoxicity in two human hepatocellular carcinoma cell lines (HepB3 and HepG2) with high and low CD44 expression was investigated; in vivo, the effect on liver metastases originating from intrasplenic implants of Lewis lung carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 23 publications
2
54
0
Order By: Relevance
“…Intraperitoneal and subcutaneous injection of butyric acid conjugates in intrasplenic hepatocellular carcinoma or melanoma mouse models resulted in fewer liver metastases. 57 Intratumoral treatment of non-small cell lung carcinoma bearing mice showed a decrease in the number of metastatic colonies in the lung. 64 However, intravenous injection resulted in rapid accumulation in clearance organs.…”
Section: B Hyaluronan Conjugates As Drug Carriersmentioning
confidence: 99%
“…Intraperitoneal and subcutaneous injection of butyric acid conjugates in intrasplenic hepatocellular carcinoma or melanoma mouse models resulted in fewer liver metastases. 57 Intratumoral treatment of non-small cell lung carcinoma bearing mice showed a decrease in the number of metastatic colonies in the lung. 64 However, intravenous injection resulted in rapid accumulation in clearance organs.…”
Section: B Hyaluronan Conjugates As Drug Carriersmentioning
confidence: 99%
“…Using HA, the natural binding partner of CD44, several drugs have been coupled to HA to be transported selectively to transformed cells: HA-But, a hyaluronic acid esterified with butyric acid, showing promising effects on malignant lesions of the liver [140], HA-cross-linked cisplatin displaying superior pharmacokinetics and pharmacodynamics to free cisplatin [141], HA-containing liposomes carrying mitomycin C [142], and paclitaxel targeting the malignant cells via CD44/HA interactions in cell lines [143] and in a human ovarian carcinoma nude mouse xenograft model. [144].…”
Section: Experimental Antagonization and Drug Resistancementioning
confidence: 99%
“…Meanwhile, CD44v6 is also expressed in both fetal and mature lung, being associated with epithelial stem cells (Jijiwa et al, 2011). Nowadays, several studies have demonstrated that CD44v6 was correlated with the prognosis of ovarian cancer (Shi et al, 2013), colorectal cancer (Wielenga et al, 1993), gastric carcinoma (Mayer et al, 1993), osteosarcoma (Deng et al, 2013), breast cancer (Kaufmann et al, 1995), bladder cancer (Omran et al, 2012) and liver cancer (Coradini et al, 2004). What's more, it has been reported that CD44v6 can contribute to both PI3K/Akt and MAPK activation, which can regulate the extracellular matrix, promote cell motility, and suppress cancer apoptosis (Marhaba et al, 2005;Jung et al, 2011).…”
Section: Introductionmentioning
confidence: 99%